Internal and external interfaces in bilingual language development: Beyond structural overlap - Sorace, Antonella; Serratrice, Ludovica (The international journal of bilingualism : cross-disciplinary, cross-linguistic studies of language behavior, 2009)
This article deals with the interface between syntax and discoursepragmatics/semantics in bilingual speakers. Linguistic phenomena at the interface have been shown to be especially vulnerable in both child and adult bilinguals; here we explore four variables that contribute to this vulnerability to different extents depending on the nature of the interface: underspecification, cross-linguistic influence, quantity and quality of the input, and processing limitations. We investigate the role played by the aforementioned variables in two recently completed studies. One compares the performance of English— Italian and Spanish—Italian bilingual children, monolingual English- and Italian-speaking children and adults on forced-choice grammaticality tasks on the distribution of overt and null subject pronouns in Italian and in English. The second explores bilingual and monolingual speakers’ sensitivity to the presence of definite articles in specific and generic plural noun phrases in Italian and in English. We show that over and above structural overlap, other factors must be We show that over and above structural overlap, other factors must be included to account for differences in the behavioural data in the two tasks and in different populations of bilinguals and monolinguals. We argue that processing factors play a non-trivial role in the difficulty encountered by bilinguals in coordinating syntax with contextual discourse-pragmatic information, regardless of the absence or presence of partial structural overlap. In the case of the internal coordination between syntax and semantics, processing factors may be less likely to affect bilinguals’ performance, while the extent of structural overlap and the associated internal formal features seem to play a more important role.